2008
DOI: 10.1111/j.1442-1984.2008.00228.x
|View full text |Cite
|
Sign up to set email alerts
|

Demographic genetics of American beech (Fagus grandifolia Ehrh.) IV. Development of genetic variability and gene flow during succession in a coastal plain forest in Maryland

Abstract: Genetic recovery of an American beech (Fagus grandifolia) population in deciduous forests that were once pastures was studied using 16 allozyme loci from 410 individuals in a 600 m ¥ 600 m study plot in Maryland, USA. We also examined the spatio-temporal genetic structure of the American beech population at a regional scale. Overall genetic diversity of mature trees was measured by estimating average heterozygosity (H = 0.156). Rare alleles were observed in five loci, Lap, 6Pdgh3, Pgi, Adh1 and Got3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 53 publications
(96 reference statements)
0
8
0
Order By: Relevance
“…Thus, neighbourhood area reflects variation in net dispersal distances of individuals from their natal source (King & Murtaugh, 1997). Wright's neighbourhood area circle contains 86.5% of individuals dispersing from its centre per generation, and its radius is 2 σ (Wright, 1946; Boshier et al , 1995; King & Murtaugh, 1997; Kitamura et al , 2008). Therefore, the radius, which represents a measure of gene flow, can be calculated from an estimate of 4 πDσ 2 if an independent demographic estimate of D can be obtained (Rousset, 1997; Sumner et al , 2001).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, neighbourhood area reflects variation in net dispersal distances of individuals from their natal source (King & Murtaugh, 1997). Wright's neighbourhood area circle contains 86.5% of individuals dispersing from its centre per generation, and its radius is 2 σ (Wright, 1946; Boshier et al , 1995; King & Murtaugh, 1997; Kitamura et al , 2008). Therefore, the radius, which represents a measure of gene flow, can be calculated from an estimate of 4 πDσ 2 if an independent demographic estimate of D can be obtained (Rousset, 1997; Sumner et al , 2001).…”
Section: Methodsmentioning
confidence: 99%
“…They found that individual heterozygosity positively affected seedling longevity in P. jezoensis . As a matter of course, the survival or death of genetically related individuals may affect the spatial genetic structure of the later life-stages ( Kitamura et al, 2008 ). However, the previous study by Okada et al (2015) did not investigate P. jezoensis FSGS or seed dispersal patterns, which may be expected to strongly reflect a lack of consistent opportunities for regeneration on CWD.…”
Section: Introductionmentioning
confidence: 99%
“…Presence of populationspecific cpSSRs haplotypes was observed also by VEN- DRAMIN et al (2000) in other parts of Norway spruce distribution in Europe. This characteristic seems to be a general peculiarity of conifer species (PROVAN et al, 1998) and within species differentiation among different sample cohorts within population was observed also in Populus and Fagus (LITTLE and DALE, 1999, TAKENAKA et al, 2002, KITAMURA et al, 2008. The proportion of reported population-specific haplotypes ranged between 40 % in Abies alba and 89 % in halepensis-complex pines .…”
Section: Discussionmentioning
confidence: 86%